Developing Next-Generation Genome Editing Tools - Gandadireja, Andrianto Prayogo (Curtin University, 2024)
Genome editing is a revolutionary biotechnological field allowing scientists to modify DNA with precision. However, current technologies remain limited and there is a need to explore new genome editing techniques that may provide alternatives to the existing techniques, which is the focus of this thesis. Here we proposed and explored three relatively new systems, namely, prokaryotic argonautes, next-generation adenine base editors, and mitochondrial RNA deaminases, which we have characterised and improved in this work.